Antitrust policy in health care markets - Angerhofer, Tirza J.; Blair, Roger D.; Durrance, Christine Piette (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
Health care costs in the United States are much higher than in other countries. These cost differences can be explained in part by a lack of competition in the United States. Some markets, such as pharmaceuticals and medical equipment, have elements of monopoly. Other markets, such as health insurance, have elements of monopsony. Many other markets may be subject to collusion on prices, such as generic drugs, or wages, such as the nurse labor market. Lawful monopoly and monopsony are beyond the reach of antitrust laws, but collusion is not. When appropriate, vigorous antitrust enforcement challenging anticompetitive conduct can aid in reducing health care costs. This book addresses monopoly, monopsony, cartels of sellers and buyers, horizontal and vertical merger policy, and antitrust enforcement through private suits as well as the efforts of the antitrust Agencies. The authors demonstrate how enforcing antitrust laws can ultimately promote competition and reduce health care costs.
Health Care Markets and Competition Policy -- Antitrust Policy in the United States -- Patents and Monopoly Pricing of Pharmaceuticals -- Patents and Exclusionary Product Hopping -- Bundled Discounts and PeaceHealth -- Collusion in Health Care Markets -- Collusion in Generic Drug Markets -- The Hatch-Waxman Act, Patent Infringement Suits, and Reverse Payments -- The Alleged Insulin Conspiracy -- Licensing of Health Care Professionals -- Monopsony, Dominant Buyers, and Oligopsony -- Countervailing Power -Physician Collective Bargaining -- Group Purchasing Organizations, Monopsony, and Antitrust Policy -- Collusion in the Nurse Labor Market -- Collusion in the Oocyte Market -- No-Poaching Agreements and Antitrust Policy -- The Economics of Horizontal Mergers -- Horizontal Merger Policy -- The Economic Theory of Vertical Integration -- Vertical Merger Policy.
Title from publisher's bibliographic system (viewed on 24 Nov 2022).
Keywords: Medical economics -- United States; Antitrust law -- United States